2022
DOI: 10.1084/jem.20211498
|View full text |Cite|
|
Sign up to set email alerts
|

PERK reprograms hematopoietic progenitor cells to direct tumor-promoting myelopoiesis in the spleen

Abstract: The spleen is an important site of hematopoietic stem/progenitor cell (HSPC) preconditioning and tumor-promoting myeloid cell generation in cancer, but the regulatory mechanism remains unclear. Here, we found that PKR-like endoplasmic reticulum kinase (PERK) mediated HSPC reprogramming into committed MDSC precursors in the spleen via PERK–ATF4–C/EBPβ signaling. Pharmacological and genetic inhibition of this pathway in murine and human HSPCs prevented their myeloid descendant cells from becoming MDSCs even with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Furthermore, PERK activation was observed in splenic HSPCs of patients with hepatocellular carcinoma and gastric cancer, and correlated with myeloid cell abundance. Overall, this indicates PERK as a promising drug target to prevent cancer immune evasion ( 51 ). This study also supports the specialized role of the splenic environment and the aberrant signaling events in splenic HSPCs as drivers of cancer associated myelopoiesis in hepatocellular carcinoma ( 51 ), although it remains to be explored to what extent the same mechanisms apply in other cancer models.…”
Section: Aberrant Myelopoiesis In Cancer: Roles and Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, PERK activation was observed in splenic HSPCs of patients with hepatocellular carcinoma and gastric cancer, and correlated with myeloid cell abundance. Overall, this indicates PERK as a promising drug target to prevent cancer immune evasion ( 51 ). This study also supports the specialized role of the splenic environment and the aberrant signaling events in splenic HSPCs as drivers of cancer associated myelopoiesis in hepatocellular carcinoma ( 51 ), although it remains to be explored to what extent the same mechanisms apply in other cancer models.…”
Section: Aberrant Myelopoiesis In Cancer: Roles and Mechanismsmentioning
confidence: 99%
“…These studies further demonstrated the accumulation of splenic HSPCs and myeloid progenitors in human cancer patients ( 49 , 50 ), which correlated with myeloid cell expansion and in gastric cancer cohorts also with poor prognosis ( 50 ). Recently scRNA-seq of HSPCs (Lin - cKit + Sca1 + ) from the spleen and bone marrow in the orthotopic Hepa1-6 HCC mouse model demonstrated a strong expansion of myeloid biased cells in the spleen, resembling the MPP3 subset of bone marrow HSPCs, with the expression of many genes indicative of myeloid lineage priming ( 51 ). In contrast, in mice transgenic for a photoconvertible protein KikGR that allows to ‘timestamp’ myeloid cells with surgery and violet light exposure, subcutaneous inoculation of syngeneic LLC lung adenocarcinoma cells demonstrated that the bone marrow rather than spleen remained the major source of monocytes, including those infiltrating the tumors ( 52 ).…”
Section: Aberrant Myelopoiesis In Cancer: Roles and Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…In glioblastoma where IRE1 somatic mutations have been linked to shorter patient survival, the IRE1 signaling dictates two distinct tumor phenotypes, with XBP1s driving the protumorigenic program, while RIDD activity attenuates it [ 121 ]. Likewise, constitutive activation of the PERK pathway has been linked to carcinogenesis and metastasis in different cancer types [ 122 , 123 ] (reviewed in: [ 124 ]). However, depending on the gene dose, PERK can function as either a tumor suppressor (when haploinsufficient) or a proadaptive tumor promoter [ 125 ].…”
Section: Therapeutic Outlook and Conclusionmentioning
confidence: 99%